Uncovering the Secrets of the 2023 Box Office: Analysis of Factors Affecting the Success of the Top 200 Films Using the Linear Regression Method - Lase, Yuyun; Claudia, Sindi; Lingga, Ichan; Ariyudha, Dimas (Yayasan Asmin Intelektual Berkah, 2024)
The film industry plays a crucial role in the global economy and popular culture, realizing creative outcomes through complex processes involving production to marketing. This research analyzes the factors influencing the success of the top 200 films at the Box Office in 2023 using linear regression. Independent variables such as film ratings, number of theaters, and distributors are examined in relation to total gross revenue. The dataset processed for this research consists of 200 data points specifically for the year 2023, sourced from Kaggle and processed with Python in Google Colab. The analysis revealed that films with a rating of 7.0 and above averaged a total gross revenue of approximately 100 million, while those rated below 7.0 averaged around 50 million, indicating a negative correlation between film ratings and gross revenue. Additionally, films shown in an average of 2,000 theaters grossed approximately 150 million, demonstrating a positive correlation between the number of theaters and gross income. The analysis also indicated that films distributed by major companies tend to have higher grosses, with the top distributors achieving an average gross of 120 million compared to 70 million for smaller distributors. Nonetheless, this analysis highlights the complexity of other factors influencing a film's success. Further research is needed for a better understanding. The relevance of these findings for the film industry lies in supporting strategic decision-making and the development of more sophisticated analytical methodologies.